(untitled) (Indian Journal of Child Health, 2020)
Background: As there is a tendency for early discharge from a hospital, some babies may develop significant neonatal jaundice at home, which may go unrecognized and cause subclinical damage to the growing brain. If such babies could be identified early, their discharge can be postponed for timely and better management. Objectives: The objectives of the study were to evaluate the umbilical cord bilirubin (UCB) levels as a predictor for hyperbilirubinemia in full-term and near-term newborns up to the 3rd day of life. Materials and Methods: A prospective cohort study was carried out in a tertiary care hospital in South India. Data were collected from the enrolled cases by a pre-designed proforma. Statistical analysis was carried out with the help of statistical measures, such as percentages and proportions and the sensitivity, specificity, and negative and positive predictive values (NPV and PPV). Results: A total of 301 newborns were enrolled. A cutoff UCB 2 mg/dl had 94% sensitivity, 93% specificity, 61% PPV, and 99% NPV. A total of 61% of neonates who had UCB levels ?2 mg/dL required phototherapy by the 3rd day of life. However, 99% of neonates who had UCB <2 mg/dL did not require phototherapy, and these infants with low risk of hyperbilirubinemia could be discharged early from the hospital. Conclusion: The cutoff value of 2 mg/dL of UCB with 94% sensitivity and 93% specificity canbe used as a predictor for developing subsequent hyperbilirubinemia.